SPECIES DIVERSITY OF BIRDS OF PREY IN HADEJIA NGURU WETLANDS, NIGERIA - Sabo Babura, Bashir; Muhammed, Salisu; Mafara, Sa'adu Abubakar (FUDMA JOURNAL OF SCIENCES, 2022)
The study aimed to determine the distribution, diversity and abundance of birds of prey in Hadejia Nguru wetlands Nigeria, carried out in March to August, 2021, with a view to providing information in a bid to establish a baseline for conservation for this group of birds. The Hadejia-Nguru Wetlands (HNWs) is a Ramsar site and an Important Bird Area (IBA) being recognized nationally and internationally as an ecological area for resident, inter-African and Palearctic migrant bird species in sub-Sahara region, Nigeria. Transect line method was used for the bird survey. This involved moving slowly along the transect line and recording all birds seen and detected in and around the transect line. The survey was carried out for a period of six (6) months using transect line method and each site was surveyed twice every month during the study period. Bird observation was carried out twice daily; morning between 6:00 to 10:00 a.m. and evening between 4:00 to 6:30p.m by walking slowly along the transect line. Birds were counted as birds seen and birds inflight were also counted. Richness index (RI) and t-test were used for data analysis. The total number of birds was calculated as the number of birds seen plus the number of birds heard. Transect line survey method detected a total of 1,562 individual birds of prey that belong to twenty four (24) species of 2 families. Accipitridae with 20 species is the richest family in species number and Falconidae with
Keywords: Diversity, wetlands, birds, transect line